2021
DOI: 10.1186/s13046-021-02009-2
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Transglutaminase 2 interacts with topoisomerase II⍺ to promote DNA damage repair in lung cancer cells

Abstract: Background To block repairs of DNA damages, especially the DNA double strand break (DSB) repair, can be used to induce cancer cell death. DSB repair depends on a sequential activation of DNA repair factors that may be potentially targeted for clinical cancer therapy. Up to now, many protein components of DSB repair complex remain unclear or poorly characterized. In this study, we discovered that Transglutaminase 2 (TG2) acted as a new component of DSB repair complex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…With the continuous development of biotechnology, complex models including carcinogenic induction model, genetically engineered mouse model and PDX model have emerged, which can make up for the above de ciencies. (39)(40)(41) In this study, we rstly used CDX model, and found that tumors derived from PRDM15-KD cells are more sensitive to radiotherapy than tumor derived from PRDM15-NC cells. However, neither the subcutaneous model nor in situ rectal cancer model can re ect the real environment.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…With the continuous development of biotechnology, complex models including carcinogenic induction model, genetically engineered mouse model and PDX model have emerged, which can make up for the above de ciencies. (39)(40)(41) In this study, we rstly used CDX model, and found that tumors derived from PRDM15-KD cells are more sensitive to radiotherapy than tumor derived from PRDM15-NC cells. However, neither the subcutaneous model nor in situ rectal cancer model can re ect the real environment.…”
Section: Discussionmentioning
confidence: 93%
“…Co-immunoprecipitation were performed to determine the interaction between proteins after irradiation as previous described (19). Brie y, for co-IP, eight hours after HCT116 cells were irradiated at a dose of 8 Gy, proteins were extracted.…”
Section: Co-immunoprecipitation (Co-ip)mentioning
confidence: 99%
“…However, these components play an important role in tumor resistance, invasion, metastasis and recurrence. With the continuous development of biotechnology, complex models including carcinogenic induction model, genetically engineered mouse model and PDX model have emerged, which can make up for the above deficiencies [ 40 42 ]. In this study, we firstly used CDX model, and found that tumors derived from PRDM15-KD cells are more sensitive to radiotherapy than tumor derived from PRDM15-NC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Co-immunoprecipitation were performed to determine the interaction between proteins after IR as previous described [ 19 ]. Briefly, for Co-IP, 8 h after HCT116 cells were irradiated at a dose of 8 Gy, proteins were extracted.…”
Section: Methodsmentioning
confidence: 99%
“…There is substantial evidence that there are individual differences in the ability of endogenous and exogenous carcinogens to DNA damage, which contributes to cancer risk 6 . The DNA repair capacity of patients with lung cancer is lower than that of normal controls, which further increases the risk of lung cancer 7,8 …”
Section: Synchronous Multiple Lung Cancers Metachronous Multiple Lung...mentioning
confidence: 99%